Relationship between microbes and the environment for sustainable ecosystem services. - Samuel, Jastin; Kumar, Ajay, PhD; Singh, Joginder, 1973- (Elsevier, 2023)
Relationship Between Microbes and Environment for Sustainable Ecosystem Services, Volume Three: Microbial Tools for Sustainable Ecosystem Services promotes advances in sustainable solutions, value-added products, and fundamental research in microbes and the environment. Topics include advanced and recent developments in the use of microbes for sustainable development. Volume Three includes concepts and applications of microbes in ecosystem services, with a focus on sustainable practices. The book will include case studies and utility of microbes on both geographical and production system-wide considerations. This book provides reference information ranging from the description of various microbial applications for the sustainability in different aspects of food, energy, environment industry and social development. This book will be helpful to environmental biotechnology scientists, industrial professionals and experts working in the field of microbiology.